2018
DOI: 10.1155/2018/1359626
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Risk of Laparoscopy-Assisted Gastrectomy by Comparing Visceral Fat Area and Body Mass Index

Abstract: Propose The purpose of this study was to compare the accuracy of visceral fat area (VFA) and body mass index (BMI) in predicting the risk of laparoscopic-assisted gastrectomy. Methods Clinicopathological and imaging data of 133 patients who underwent laparoscopy-assisted gastrectomy were recorded, including 17 cases of conversion to open surgery. The remaining 116 patients were retrospectively analyzed after we excluded 17 patients who had been transferred to laparotomy. The patients were divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…PMI is a simple but reliable method of prognostic evaluation similar to SOFA. Body composition has recently been reported as a risk factor or prognostic factor for postoperative complications [3,5,24,25]. In particular, skeletal muscle mass is considered important [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…PMI is a simple but reliable method of prognostic evaluation similar to SOFA. Body composition has recently been reported as a risk factor or prognostic factor for postoperative complications [3,5,24,25]. In particular, skeletal muscle mass is considered important [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Does obesity affect the prognosis of cancer patients? Visceral fat area, as an evaluation index of obesity, can evaluate operative difficulties and is reportedly associated with post-operative complications (29,30). However, BMI has little to do with long-term prognosis in the present study (P > 0.05).…”
Section: Discussionmentioning
confidence: 50%
“…Recently, increasing attention has been paid to VFA and BMI as obesity indexes. Previous studies found VFA to be superior to BMI in accurately and effectively predicting the effect of obesity on adverse postoperative outcomes [22][23][24] after radical colectomy as well as radical gastrectomy. However, all the studies focused on the comparison of two indications and whether VFA is a better parameter than BMI remains controversial.…”
Section: Discussionmentioning
confidence: 99%